Struktur Komunitas Makrobentos Sebagai Bioindikator Kualitas Perairan di Kecamatan Sayung, Demak, Indonesia - Iqbal, Fakhrezi Muhammad; Hidayat, Jafron Wasiq; Muhammad, Fuad (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Sayung Subdistrict is a densely populated area and has many industrial areas. It was expected that it has produced pollutant waste that enter the aquatic environment. The existence of these wastes can affect the quality of the waters and lives therein. This study aims to determine the quality of the waters by assessing the structure of the macrobenthos community temporally and spatially which are related to the physical-chemical parameters of the water. The data collection of macrobenthos and substrate waters were carried out at 5 station considered as represent variety of waters bodies in Sayung. Samples were taken 2 times, in dry season and rainy seasons. Water parameters measured including DO, salinity, pH, turbidity, and temperature, while sediments are analyzed for the grain size of sediment and organic matter content. The results from macrobenthos analysis found 20 species. The most commond macrobentos found Metapenaeus monocerus, Cerethidea cingulata,Telescopium telescopium and Sesarma sp. Macrobenthos diversity index ranges from 0.59 to 1.76; Evenness index ranges from 0.78 to 0.96; and the dominance index ranges from 0.19 to 0.59. Diversity index value include the moderate criteria, which indicates a disturbance in Sayung waters. The results of multiple linear regression test showed that DO-silt parameter has a strong influence on the abundance of macrobenthos. The abundance of species Cerithidea cingulata at the research site can be used as bioindicators of contamination organic matter. Generally these waters still supports aquaculture